One Pot Synthesis of Benzopyrans in Water as Green Solvent - Kumar, Sunil; Saifuddin Khalid, Md.; Udupi, R.H. (Asian Journal of Chemistry, 2010)
A convenient synthesis of polyfunctionalized benzopyran derivatives using tricaprylyl methyl ammonium chloride (aliquate-336) as a catalysts (10 mol %) is described. The catalyst found to be an effective for the synthesis of various benzopyran derivatives. The method has several advantages such as good to excellent yields, minimum environmental impact and simplest work up procedure.